(untitled) (Baltic Journal of Sport and Health Sciences, 2026)
Purpose: The primary purpose of this study is to evaluate the impact of service quality on the loyalty of fitness club clients. The research addresses the question: ‘what is the impact of service quality on fitness club client loyalty?’. Methods: This quantitative study employed a methodology involving the analysis of scientific literature, a survey, and statistical analysis to assess the relationship between service quality and customer loyalty in Lithuanian fitness clubs. Results: The study found that service quality is a dynamic and subjective phenomenon formed by comparing consumer expectations with their experiences. Loyalty in the context of fitness clubs is manifested through repeated memberships, recommendations to others, and remaining faithful despite competitive alternatives. Research indicates a strong link between service quality and customer loyalty, where high-quality services foster satisfaction, trust, and commitment. The results of this study revealed that while customer expectations often exceed their actual experiences, all dimensions of service quality are significantly related to loyalty, with price, fitness programmes, and equipment having the strongest impact. Conclusion: This research contributes to the understanding of the key service quality dimensions that influence customer loyalty in the fitness club sector in Lithuania. The findings offer practical implications for fitness club managers seeking to enhance customer retention and loyalty by focusing on improving service quality, particularly in the areas of pricing, programme offerings, and facility equipment.